Digital dice / Mohd Farahan Mond Anuar and Saifull Bahri Muerkan - Mond Anuar, Mohd Farahan; Muerkan, Saifull Bahri (2001)
Final project is a part of course structure as a fulfill for students in their final year. The project is compulsory to us as a final year student for course Diploma In Electrical Engineering, The purpose of this project is to produces a student a main power with a very high skill and able to handle a responsibility given like a project. They should prepare to deliver a creativity ideas and good interpersonal image to their future employer. It can make students used all of their knowledge, creative and skill to purpose, create and trouble shoot the project. It is because all of the theory and skills, they have learned from the project 1 and project 2 are used. As the time change, the way of life is also change with them. Nowadays the rapid changes as quality of life require new technologies so as to fixed with them The main purpose of this project is actually based on the needs of some peoples nowadays to overcome obstacle in their everyday life. This project replace a traditional dice into digital dice. The display is connected to the receiver circuit. When receiver circuit received a signal from transmitter, the display will show the rotation number between 1 until 9 is continuously when the switch is pressed ( on). The number will stop randomly when is release ( off). Therefore, This project could be taken as a game dice like a DAM CINA, DAM ULAR or the total movement in a board game. So, we expect that it can be alter and convert it to a children game in the future.